Habitability on moons of planetary systems: a new frontier - Fonseca, Vitória Bellecerie; Pacheco, Eduardo Janot (Cadernos de Astronomia, 2022)
Space flights carried out in the 80-2000s brought immense advances in our knowledge of the physical and chemical conditions existing in large moons of the gas giant planets in the Solar System. Close flybys, especially of Titan, Europa and Enceladus revealed surprising features in these moons and made it possible to compose a very detailed picture of their surfaces and interiors and of the atmosphere, in the case of Titan. The discovery of subsurface oceans in almost all the large moons of Saturn and Jupiter opened up the extraordinary prospect that extremophile life could exist in these places, something previously unknown. In this article, we present characteristics, especially about these three moons, and arguments that defend this thesis: a new habitability zone seems to exist in the rocky satellites of gas giant exoplanets, multiplying the possibility of extremophile life across the Milky Way.